Optimizing Electrical Energy Use through AI: An Integrated Approach for Efficiency and Sustainability - Heni Nurhaeni; Ariana Delhi; Ora Plane Maria Daeli; Sheila Aulia Anjani; Natasya Aprila Yusuf (International Transactions on Artificial Intelligence, 2024)
The increasing need for electrical energy in the modern era requires innovative steps to optimize its use. This research explores the application of Artificial Intelligence (AI) in optimizing the use of electrical energy with a focus on efficiency and sustainability. Using a quantitative approach with a descriptive-analytical design, this research collects data from various sources, including surveys, interviews and secondary literature. The results show that the application of AI can reduce electrical energy consumption by 20-30% in various sectors, such as the manufacturing industry and smart households. In addition, AI contributes significantly to reducing carbon emissions, with a 25% reduction in emissions in the manufacturing industrial sector. AI also demonstrated higher energy efficiency compared to traditional methods, with an average improvement of 25%. These findings imply that AI not only improves energy efficiency but also supports environmental sustainability through reducing carbon emissions. Practical recommendations include investment in AI technologies for energy management and policy support to accelerate AI adoption. This research provides the basis for further studies to explore the potential of AI in other sectors and its long-term economic impact. Thus, the application of AI in electrical energy management is expected to contribute significantly to energy efficiency and global sustainability.